Postdischarge Decolonization of Patients Harboring MRSA USA300 Strains: Secondary Analysis of the CLEAR Trial. (October 2020) - Gussin, Gabrielle M.; Heim, Lauren; Tjoa, Thomas; Miller, Loren; Gillen, Daniel L.; Sater, Mohamad; Grad, Yonatan H.; Singh, Raveena D.
Abstract : Background: The Changing Lives by Eradicating Antibiotic Resistance (CLEAR) Trial was a trial of 2, 121 recently discharged methicillin-resistant Staphylococcus aureus (MRSA) carriers randomized to MRSA education plus a 5-day decolonization regimen repeated twice monthly for the 6 months following discharge versus MRSA education alone. Decolonization resulted in a 30% reduction in MRSA infection and a 17% reduction in all-cause infection (Huang SS et al, NEJM, 2019) in the year following discharge. We pursued an evaluation of USA300 carriers to determine whether the decolonization benefit differed for this strain type. Methods: A secondary analysis of the CLEAR randomized controlled trial (RCT) was performed, limiting the cohort to participants known to harbor USA300 at or within 30 days of enrollment and who attended all follow-up visits in the year following discharge. Within this subset, we conducted a time-to-event analysis using unadjusted and adjusted Cox proportional-hazard models. Variables in adjusted analyses included demographic data, insurance type, presence of coexisting conditions or medical devices at enrollment, hospitalization or residence in a nursing home in the year before enrollment, receipt of anti-MRSA antibiotics, protocol adherence, and randomization strata. Results: USA300 was identified in 420 of the 783 participants who attended all visits and had strains genetically tested. MRSA infections occurred in 27 of 207 education group participants (0.149 per person year) and in 19 of 213 decolonization group participants (0.099 per-person year). Point estimates from the unadjusted hazard ratios of infection reduction were similar (0.59; 95% CI, 0.32–1.09) to the full trial population (0.61; 95% CI, 0.44–0.85), suggesting nondifferential benefit for the USA300 strain type. Adjusted models were highly similar. Conclusions: The reduction in MRSA infection associated with postdischarge decolonization in the subgroup of participants who harbored the USA300 strain-type was consistent with overall trial findings. Although the original trial was not powered for the evaluation of a USA300 subset, this RCT provides a valuable design for assessing the magnitude of strain-specific responsiveness to decolonization during a time when national rates of MRSA invasive disease have plateaued and USA300 is responsible for an increasing proportion of infections. These data suggest that postdischarge decolonization should be similarly effective in carriers of either USA300 or healthcare-associated MRSA strains. Funding: None Disclosure: Gabrielle M. Gussin, Stryker (Sage Products): Conducting studies in which antiseptic product is provided to participating hospitals and nursing homes. Clorox: Conducting studies in which antiseptic product is provided to participating hospitals and nursing homes. Medline: Conducting studies in which antiseptic product is provided to participating hospitals and nursing homes. Xttrium: Conducting studies in which antiseptic product is provided to participating hospitals and nursing homes. Mohamad Sater, Salary-Day Zero Diagnostics.